2011
DOI: 10.1016/j.limno.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

First records, pathways and distributions of four new Ponto-Caspian amphipods in France

Abstract: International audienceIn Europe, the number of establishment of non-native species, especially from Ponto-Caspian area, has dramatically increased over the past decades and induced important changes in macroinvertebrate assemblages, mainly in large rivers. However, although many Ponto-Caspian species were established in adjacent countries, only two Ponto-Caspian amphipods were formally observed in French hydrosystems since 1996. To update our knowledge on the present distribution of the Ponto-Caspian species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The three invasive Dikerogammarus species, D. bispinosus , D. haemobaphes and D. villosus , are also ecologically similar and closely related (Müller, Schramm & Seitz, ). Dikerogammarus villosus and D. haemobaphes have invaded several rivers and canals in recent decades in Central and Western Europe including the British Isles using both the Danube‐Rhine and the Dnieper‐Vistula corridors (Bij de Vaate et al ., ; Grabowski, Jażdżewski & Konopacka, ; Labat, Piscart & Fontan, ; Gallardo & Aldridge, ; Rewicz et al ., ). Dikerogammarus villosus is, however, more successful at colonizing lakes and has a more severe impact on native and other invasive species (reviewed by Rewicz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The three invasive Dikerogammarus species, D. bispinosus , D. haemobaphes and D. villosus , are also ecologically similar and closely related (Müller, Schramm & Seitz, ). Dikerogammarus villosus and D. haemobaphes have invaded several rivers and canals in recent decades in Central and Western Europe including the British Isles using both the Danube‐Rhine and the Dnieper‐Vistula corridors (Bij de Vaate et al ., ; Grabowski, Jażdżewski & Konopacka, ; Labat, Piscart & Fontan, ; Gallardo & Aldridge, ; Rewicz et al ., ). Dikerogammarus villosus is, however, more successful at colonizing lakes and has a more severe impact on native and other invasive species (reviewed by Rewicz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although environmental factors are known to play a crucial role in the spread of many non-native invasive species (Leppäkoski et al, 2002;Labat et al, 2011), little is known about their influence on the nature and direction of species' ecological impacts ( Van der Velde et al, 2009). In addition, the strength of ecological impact is a growing concern in the context of current global changes (Bellard et al, 2013), as the resulting changes in environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bioclimatic predictive modelling has shown that almost 60% of Great Britain is suitable for its continued and rapid spread (Gallardo, Errea & Aldridge, 2012) and this British invasion was just the latest range expansion of this species, which is already present in at least 17 European countries. These include the zebra mussel Dreissena polymorpha (Pallas, Vaate et al, 2002;Leuven et al, 2009;Messiaen et al, 2010;Labat, Piscart & Fontan, 2011). These include the zebra mussel Dreissena polymorpha (Pallas, Vaate et al, 2002;Leuven et al, 2009;Messiaen et al, 2010;Labat, Piscart & Fontan, 2011).…”
Section: Introductionmentioning
confidence: 99%